2016
DOI: 10.1002/dev.21449
|View full text |Cite
|
Sign up to set email alerts
|

Infant hair cortisol: associations with salivary cortisol and environmental context

Abstract: Early chronic stress has enduring implications for physical and mental health outcomes. Hair cortisol concentration (HCC) has emerged as a marker of cumulative cortisol exposure, yet HCC in infants is not well understood. We examined how infant HCC relates to widely used basal salivary cortisol measures, maternal HCC, and environmental context in 111 infants assessed at 6 and 12 months of age. Maternal HCC at 6 and 12 months was correlated with infant HCC at 12 months. At 12 months, infant HCC was positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 66 publications
9
81
1
1
Order By: Relevance
“…In 11 studies that examined between one and four indicators of adversity, four reported no associations with hair cortisol (Boeckel et al, 2017;Flom, et al, 2017;Gerber et al, 2017;Olstad et al, 2016), five reported associations with one indicator (Ouellette et al, 2015;Palmer et al, 2013;Ursache et al, 2017;Vaghri et al, 2013;Vliegenthart et al, 2016), and two studies reported associations with two indicators (Rippe et al, 2016;Windhorst et al, 2017). Where associations are reported, often they are not replicated by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 11 studies that examined between one and four indicators of adversity, four reported no associations with hair cortisol (Boeckel et al, 2017;Flom, et al, 2017;Gerber et al, 2017;Olstad et al, 2016), five reported associations with one indicator (Ouellette et al, 2015;Palmer et al, 2013;Ursache et al, 2017;Vaghri et al, 2013;Vliegenthart et al, 2016), and two studies reported associations with two indicators (Rippe et al, 2016;Windhorst et al, 2017). Where associations are reported, often they are not replicated by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the small sample size did not allow us to test associations by type of SAD. Lastly, ideally other tests of HPA axis activity, relating to HPA axis reactivity and rhythmicity, should have been included too [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Typically, no more than 3 cm is examined as cortisol leaches from the hair with washing and hair treatments. In infants, hair cortisol is positively related to waking and bedtime levels and total magnitude of cortisol across the day, but not the diurnal slope (Flom, St. John, Meyer, & Tarullo, ).…”
Section: Neurophysiology Of Stressmentioning
confidence: 99%